Environmental Impacts and the Food vs. Fuel Debate: A Critical Review of Palm Oil as Biodiesel - Indra Purnama; Anisa Mutamima; Muhammad Aziz; Karna Wijaya; Iffana Dani Maulida; Junaidi Junaidi; Karmila Sari; Irwan Effendi; Isna Rahma Dini (GCB Bioenergy)
ABSTRACT Palm oil is an efficient feedstock for biodiesel production due to its high oil yield and cost‐effectiveness, positioning it as a key component in the global biofuel industry. However, the expansion of oil palm plantations has raised substantial environmental and socio‐economic concerns. This review critically assesses the environmental impacts of palm oil biodiesel, including greenhouse gas emissions, deforestation, biodiversity loss, and the degradation of water and soil resources. Additionally, it explores the “food versus fuel” debate, emphasizing how competition for land and resources between biodiesel production and food cultivation affects global food security, particularly in developing nations. What distinguishes this review is its focus on Southeast Asian producer countries, particularly Indonesia and Malaysia, where biodiesel policies and land‐use changes intersect with food and environmental systems in unique ways. Unlike previous studies, this article delves into the often‐overlooked consequences of peatland conversion, highlighting its role in exacerbating carbon emissions and biodiversity loss. By providing a detailed analysis of the socio‐economic trade‐offs and sustainability challenges linked to palm oil biodiesel, the review offers insights into the complex interplay between renewable energy, food security, and environmental stewardship. It also evaluates technological innovations and best practices that can mitigate negative impacts. Furthermore, the review critically examines certification initiatives like the roundtable on sustainable palm oil (RSPO) and the indonesian sustainable palm oil (ISPO) and their effectiveness in promoting sustainable practices. By integrating case studies, this article demonstrates practical applications of these principles, offering actionable recommendations for policymakers, industry stakeholders, and researchers in the field.